MEMBANGUN CITRA GLOBAL MELALUI KEMANUSIAAN: EVALUASI PERSEPSI PUBLIK TERHADAP INISIATIF #TAIWANCANHELP - Wibowo, Bromo; Andi Muhammad Farid Ramadhan (CONVERGENCE: JOURNAL OF GLOBAL DYNAMICS, 2026)
This research analyzes tweet data related to the hashtag "#TaiwanCanHelp." This analysis presents data on how public perception of Taiwan's digital diplomacy is shaped thru the hashtag #TaiwanCanHelp. This data analysis is used to evaluate public sentiment toward Taiwan's role in global affairs, particularly its willingness to provide assistance to other countries. The data analysis also reveals the topics and contexts in which this hashtag is used, providing insights into public perception of Taiwan's contributions. The results of this study are expected to provide a clearer picture of how Taiwan's initiatives in helping other countries are received and responded to by the international community.